Behaviour of Mixed Expansive Soil and Additive Minerals as Subgrade Layer. Issue 1 (August 2021) - Sitepu, F; Harianto, T; Ridwan, R; Marfuah, N
Abstract: South Sulawesi is one of eastern Indonesia area covered with coastal line which have growth fast of industries. Infrastructure builds and developed in a row of industries population. Most coastal are lowland areas with expansive soil as primary soil forms. Exhaustive laboratory test conducts for clay taken from lowland area in south Sulawesi and lime up to 10% and volcanic up to 25% as stabilizers to know the Physical-mechanical properties and mineralogical when the expansive soil stabilized. The extensive soil stabilized with 5% lime + 15% Volcanic ash presents better performance and pass the roadbed materials requirements. Chemical reactions between soil and the stabilizers increase the pH and electrical conductivity. X-ray diffraction (XRD) and transmission electron microscope (TEM) confirmed new cementing agents' findings regarding the results of chemical reactions. An explicit effect on controlling the soil deformation and the moisture change shows by the expansive soil stabilized with 5% lime + 15% volcanic ash. The research results find the optimum combination of stabilizers to reduce cost to improve expansive soil from the South Sulawesi lowland area.